The potential of carbon storage in the biomass of Jujube trees distributed in the historic site of Phra Nakhon Si Ayutthaya district, Phra Nakhon Si Ayutthaya province - Eiamsa-ard, Pradinunt; Suksamang, Chonthicha; Tantipanatip, Watcharaporn (RMUTSB ACADEMIC JOURNAL, 2025)
Plants play an important role in absorbing and sequestering atmospheric carbon dioxide through the process of photosynthesis and storing carbon in the form of biomass. This research aimed to assess the biomass and carbon storage potential of Jujube trees across four historic sites in Phra Nakhon Si Ayutthaya District, Phra Nakhon Si Ayutthaya province, namely Ayutthaya Royal Palace (AYH1), Wat Phra Ram (AYH2), Wat Ratchaburana (AYH3) and Wat Wang Chai (AYH4). A survey of growth data, including height and diameter at breast height (DBH) for individuals exceeding 4.5cm, was conducted to assess aboveground biomass (AGB), belowground biomass (BGB), and carbon storage of the Jujube trees, which were estimated using allometric equations. The results showed a total of 619 Jujube trees, with the highest distribution observed in AYH1 (489 trees) and the lowest number recorded in AYH4 (20 trees). Additionally, regarding the growth of Jujube trees distributed within Wat Wang Chai (AYH4), they exhibited the highest average height (12.74m), stem circumference (292.85cm), and diameter at breast height (DBH) (94.11cm). The total biomass amounted to 9,294.77kg, which was divided into 7,376.80kg of AGB and 1,917.97kg of BGB, along with a total carbon storage of 4,368.54kg from a total of 619 Jujube trees. Furthermore, Wat Wang Chai (AYH4) showed the highest AGB (2,973.84kg), BGB (773.20kg), and carbon storage (1,761.11kg). This was attributed to Jujube trees having generally larger stem sizes, with their stem circumference and DBH exhibiting the highest average values.